Locomotion and Posture in Older Adults 2017
DOI: 10.1007/978-3-319-48980-3_27
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in the Neural Control of Standing Balance

Abstract: Controlling body sway while standing is an active process involving lower as well as higher neural centers. This chapter examines how the central nervous system controls undisturbed standing balance and summarizes the current knowledge concerning the effects of task difficulty and old age on postural control of standing. There is an age-related reorganization of neural control of standing, with decreased efficacy of Ia afferents to activate spinal motor neurons, increased cortical activation and corticospinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 136 publications
2
6
0
Order By: Relevance
“…These data add to the emerging view of age-related impairments in the inhibitory neural control of voluntary movement (Baudry et al 2015; Levin et al 2014; Papegaaij and Hortobágyi 2017). …”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…These data add to the emerging view of age-related impairments in the inhibitory neural control of voluntary movement (Baudry et al 2015; Levin et al 2014; Papegaaij and Hortobágyi 2017). …”
Section: Discussionsupporting
confidence: 62%
“…Under appropriate experimental controls, we found that the stereotypical H reflex depression associated with an APA in younger adults (age ~ 21) was reduced in middle-aged adults (age ~ 47) and reversed to facilitation in healthy older adults (age ~ 70). These data add to the emerging view of age-related impairments in the inhibitory neural control of voluntary movement (Baudry et al 2015 ; Levin et al 2014 ; Papegaaij and Hortobágyi 2017 ).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Besides, one exercise session may increase the conductivity of the nerves (41)(42)(43), which is part of the sensorimotor mechanism. The sensitivity of lower extremity proprioception declines with normal aging (43,44), and this decline has been associated with an increase in postural swaying (2,3,38,45,46) and with a history of falling (38). According to the study, the decrease in COP velocity after a single NPT session occurred in the ML plane under the CE condition.…”
Section: Discussionmentioning
confidence: 88%
“…The percentage of people over the age of 60 years in the global population, according to the forecast of the World Health Organization will increase from 10.0% in 2000 to 21.8% in 2050, and then to 32.2% in 2100 (1). The natural aging process is associated with poor balance ability and reduction in the joint position sensation (2,3). Women are generally weaker than men in all age groups (4,5).…”
Section: Introductionmentioning
confidence: 99%